Association between red cell distribution width/serum albumin ratio and Parkinson’s disease - Mimi Li; Yingying Xu; Zhengping Huang; Lichao Ye; Chunnuan Chen (European Journal of Medical Research)
Abstract Background The ratio between erythrocyte distribution width and serum albumin (RAR) has gained recognition as a novel composite biomarker for inflammatory processes, though its clinical significance in Parkinson's disease (PD) pathology requires further exploration. The purpose of this cross-sectional study was to investigate the relationship between RAR and PD. Methods This epidemiologic investigation utilized data from participants enrolled in the National Health and Nutrition Examination Survey (NHANES) spanning 2003–2018. Study cohorts comprised PD-diagnosed individuals and matched controls. To elucidate the RAR–PD connection, we implemented three analytical strategies: multivariable-adjusted logistic regression models incorporating sample weights, restricted cubic spline (RCS) modeling for nonlinear relationships, and stratified analyses across demographic subgroups. Comparative assessment of inflammatory biomarkers' discriminative performance was performed through ROC curve analysis, contrasting RAR against platelet–albumin ratio (PAR) and neutrophil–albumin ratio (NAR). Results The analysis encompassed 31,848 adults (297 PD cases; 31,551 controls) from the NHANES database. Quantitative analysis revealed elevated RAR measurements in PD subjects compared to controls [3.28 (0.04) vs. 3.09 (0.01), P < 0.001]. Following covariate adjustment in weighted regression models, multivariable-adjusted analyses identified RAR as an independent predictor (adjusted OR = 1.40, 95% CI 1.06–1.85, P = 0.018). RCS modeling revealed nonlinear RAR–PD associations, peaking at 3.48 (inverted U-shape). Comparative ROC analysis confirmed RAR's discriminative superiority over PAR and NAR in PD detection (P < 0.05). Conclusions As demonstrated by the research findings, RAR is strongly and independently associated with PD. RAR may serve as an indicator or screening tool for an increased risk of PD. Graphical abstract